Penanamam Mangrove dengan Media Bumbung pada Kegiatan Pengabdian Masyarakat di Wilayah Pesisir: Mangrove Planting with Bumbung Media in Community Service Activities on Coastal Areas - Ariadi, Heri; Mardiana, Tri Yusufi; Fahrurrozi, Ashari; Maghfiroh, Maghfiroh; Sulistiana, Ana; Firdausa, Della Izati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Mangrove trees have an important function for the coastal ecosystem. The purpose of this community service activity is to carry out mangrove planting activities using bamboo roof media in the coastal area of Pekalongan. The method used in this community service is field observation and social action of planting 550 A. marina mangrove seeds by 26 participants. The results of the community service show that the community service participants absolutely feel that they have obtained valuable benefits in the form of enrichment of knowledge about mangroves and valuable social experiences. The participants also feel enthusiastic about participating in the activity and want to participate again if there is a similar activity. The participants also recommended several places for future planting, such as in coastal areas that are prone to disasters, dead coastal areas, and shallow water areas that are inundated. From the results of this community service, it can be concluded that the mangrove planting activity on the coast of Pekalongan is considered very effective to be used as a model for community service activities based on social action activities or active participation carried out by community groups. This can be seen from the achievement of tangible benefits obtained from the results of the activities that have been carried out.